Mineral-driven molecular signatures of energy metabolism underpin sperm motility in buffalo - A.T. Manjunatha; R. Shalini; B.K. Binsila; B. Krishnappa; D. Rajendran; T. Athira; K. Parvathi; A. Sahoo; S. Selvaraju (Animal Reproduction Science, 2026)

Synthesis strategies, nutrient delivery mechanisms, and pathways toward sustainable agriculture via nano-fertilizers - Praveen Mallari; Venkatachalam Deepa Parvathi; V. Sathishkumar; R. B. Jeen Robert; M. Joemax Agu; M. Muthuselvi; G. S. Hikku (Journal of Crop Science and Biotechnology, 2026)

Morphological and Physiological Responses of Two Tropical Rice (Oryza sativa) Varieties to High-Temperature Stress - V. S. Anup; Pallot Sindhumole; Jiji Joseph; Deepu Mathew; M. S. Parvathi; B. R. Vishnu (Agricultural Research, 2026)

Cryopreservation of bael (Aegle marmelos L.Corr.) using encapsulated axillary buds - E. Deepa; Deepa S. Nair; Swapna Alex; K. B. Soni; M. M. Viji; B. Parvathi (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Convergence Research and Training in Computational Bioengineering: A Case Study on AI/ML-Driven Biofilm–Material Interaction Discovery - Jessica L. S. Zylla; Alain B. Bomgni; Rajesh K. Sani; Mahadevan Subramaniam; Carol Lushbough; Robb Winter; Venkataramana R. Gadhamshetty; Parvathi Chundi; Etienne Z. Gnimpieba (Biomedical Engineering Education, 2024)
Historically, research disciplines have successfully operated independently. However, the emergence of transdisciplinary research has led to convergence methodologies, resulting in groundbreaking discoveries. Despite the benefits, graduate programs face challenges in implementing transdisciplinary research and preparing students for real-world collaboration across diverse disciplines and experience levels. We propose a convergence training framework integrating project-based learning, training modules, and collaborative teaming to address this. This approach, tested in a multi-institutional workshop, proved effective in bridging expertise gaps and fostering successful convergence learning experiences in computational biointerface (material–biology interface) research. Here, biointerface research focuses on control of biomolecular interactions with technologically relevant material surfaces, which is a critical component of biotechnology and engineering applications. Positive outcomes, including conference presentations and published models, endorse the framework's application in graduate curricula, particularly for students engaging in transdisciplinary collaboration.

New-onset diabetic ketoacidosis with purpura fulminans in a child with COVID-19-related multisystem inflammatory syndrome - Parvathi Parappil; Sushant Ghimire; Apoorv Saxena; Sweta Mukherjee; B. M. John; Vishal Sondhi; P. Sengupta; Suchi Acharya (Infectious Diseases, 2022)

Transcriptome analysis of finger millet (Eleusine coracana (L.) Gaertn.) reveals unique drought responsive genes - M. S. Parvathi; Karaba N. Nataraja; Y. A. Nanja Reddy; Mahantesha B. N. Naika; M. V. Channabyre Gowda (Journal of Genetics, 2019)

Expression analysis of stress responsive pathway genes linked to drought hardiness in an adapted crop, finger millet (Eleusine coracana) - M. S. Parvathi; Karaba N. Nataraja; B. K. Yashoda; H. V. Ramegowda; H. M. Mamrutha; N. Rama (Journal of Plant Biochemistry and Biotechnology, 2013)

Feature extraction from satellite images of hilly terrains using wavelets and watersheds - K. Parvathi; B. S. Prakasa Rao; T. Venkateswara Rao; K. Mruthyunjaya Reddy (International Journal of Remote Sensing, 2010)